2006
DOI: 10.1159/000091641
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Predicts Impaired Atrial Remodeling and Occurrence of Late Postoperative Atrial Fibrillation after Surgery for Symptomatic Aortic Stenosis

Abstract: Background: Aortic stenosis (AS) and atrial fibrillation (AF) are commonly encountered in clinical practice. Natriuretic peptides (NP) are endogenous cardiac hormones, which have been shown to increase in patients with heart failure, and valvular or congenital heart disease. We aimed to determine the association between atrial NP (ANP) and late postoperative AF after surgery for AS along with temporal changes in plasma ANP levels and left atrial (LA) volumes. Methods: 22 patients (16 males/6 females, mean age:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…230 Plasma natriuretic peptide (ANP) levels are higher in symptomatic than asymptomatic patients with AS 231 and N-ANP levels predict atrial remodelling and late (2 month) post-operative AF after surgery for AS. 232 Taken together, these data support the notion that substrate-based AF is a consequence of the abnormal haemodynamics and atrial remodelling that accompany valvular heart disease. In this instance, atrial remodelling is the consequence of multiple biological processes that create structural and ultrastructural abnormalities and a change in conduction (as opposed to refractoriness) that favours the development and maintenance of AF.…”
Section: Atrial Cardiomyopathy Due To Valvular Heart Diseasesupporting
confidence: 71%
“…230 Plasma natriuretic peptide (ANP) levels are higher in symptomatic than asymptomatic patients with AS 231 and N-ANP levels predict atrial remodelling and late (2 month) post-operative AF after surgery for AS. 232 Taken together, these data support the notion that substrate-based AF is a consequence of the abnormal haemodynamics and atrial remodelling that accompany valvular heart disease. In this instance, atrial remodelling is the consequence of multiple biological processes that create structural and ultrastructural abnormalities and a change in conduction (as opposed to refractoriness) that favours the development and maintenance of AF.…”
Section: Atrial Cardiomyopathy Due To Valvular Heart Diseasesupporting
confidence: 71%
“…The present results confirm the findings of other studies showing significantly elevated levels of natriuretic peptides in various types of congenital and valvular heart diseases [3][4][5] . Other studies have shown a relationship between concentrations of natriuretic peptides and severity of heart failure [6][7][8][9][10][11][12] .…”
Section: Discussionsupporting
confidence: 92%
“…230 Plasma natriuretic peptide (ANP) levels are higher in symptomatic than asymptomatic patients with AS 231 and N-ANP levels predict atrial remodelling and late (2 month) post-operative AF after surgery for AS. 232 …”
Section: Pathology Of Atrial Cardiomyopathiesmentioning
confidence: 99%